ls = [3.5, "Python", [10,"LIST"], 3.6],ls[2][-1][1]的运行结果是:
ls = [3.5, "Python", [10,"LIST"], 3.6],ls[2][-1][1]的运行结果是:
ls = [3.5, "Python", [10, "LIST"], 3.6],ls[2][ –1][1]的运行结果是 A: L B: I C: P D: Y
ls = [3.5, "Python", [10, "LIST"], 3.6],ls[2][ –1][1]的运行结果是 A: L B: I C: P D: Y
59ls=[3.5,"Python",[10,"LIST"],3.6],ls[2][–1][1]的运行结果是 A: I B: Y C: L D: P
59ls=[3.5,"Python",[10,"LIST"],3.6],ls[2][–1][1]的运行结果是 A: I B: Y C: L D: P
59ls=[3.5,"Python",[10,"LIST"],3.6],ls[2][–1][1]的运行结果是 A: I B: Y C: L D: P
59ls=[3.5,"Python",[10,"LIST"],3.6],ls[2][–1][1]的运行结果是 A: I B: Y C: L D: P
ls = [3.5, "Python", [10, "LIST"], 3.6] print(ls[2][-1][1]) 的运行结果是 A: I B: P C: Y D: L
ls = [3.5, "Python", [10, "LIST"], 3.6] print(ls[2][-1][1]) 的运行结果是 A: I B: P C: Y D: L
ls = [3.5, "Python", [10, "LIST"], 3.6]<br/>ls[2][–1][1]的运行结果是 A: I B: P C: Y D: L
ls = [3.5, "Python", [10, "LIST"], 3.6]<br/>ls[2][–1][1]的运行结果是 A: I B: P C: Y D: L
若ls=[3.5,“Python”,[10,“LIST”],3.6],则ls[2][-1][1]的运行结果是( )。 A: I B: P C: Y D: L
若ls=[3.5,“Python”,[10,“LIST”],3.6],则ls[2][-1][1]的运行结果是( )。 A: I B: P C: Y D: L
ls = [3.5, "Python", [10, "LIST"], 3.6]ls[2][ –1][1]执行上述语句的运行结果是:( )。 A: I B: P C: Y D: L
ls = [3.5, "Python", [10, "LIST"], 3.6]ls[2][ –1][1]执行上述语句的运行结果是:( )。 A: I B: P C: Y D: L
假设ls=[3.5,”Python”,[10,”LIST”],3.6],则执行ls[2][-1][1]的结果为 A: L B: I C: P D: Y
假设ls=[3.5,”Python”,[10,”LIST”],3.6],则执行ls[2][-1][1]的结果为 A: L B: I C: P D: Y
以下代码的运行结果是: ls = [3.5, "Python", [10, "LIST"], 3.6] print(ls[2][-1][1]) A: L B: Y C: P D: I
以下代码的运行结果是: ls = [3.5, "Python", [10, "LIST"], 3.6] print(ls[2][-1][1]) A: L B: Y C: P D: I